Cardiorespiratory Abnormalities in Patients Recovering from Coronavirus Disease 2019 - Szekely, Yishay; Lichter, Yael; Sadon, Sapir; Lupu, Lior; Taieb, Philippe; Banai, Ariel; Sapir, Orly; Granot, Yoav; Hochstadt, Aviram; Friedman, Shirley; Laufer-Perl, Michal; Banai, Shmuel; et al. (Journal of the American Society of Echocardiography, 2021)
A large number of patients around the world are recovering from coronavirus disease 2019 (COVID-19); many of them report persistence of symptoms. The aim of this study was to test pulmonary, cardiovascular, and peripheral responses to exercise in patients recovering from COVID-19. Patients who recovered from COVID-19 were prospectively evaluated using a combined anatomic and functional assessment. All patients underwent clinical examination, laboratory tests, and combined stress echocardiography and cardiopulmonary exercise testing. Left ventricular volumes, ejection fraction, stroke volume, heart rate, E/e′ ratio, right ventricular function, oxygen consumption (Vo2), lung volumes, ventilatory efficiency, oxygen saturation, and muscle oxygen extraction were measured in all effort stages and compared with values in historical control subjects. A total of 71 patients were assessed 90.6 ± 26 days after the onset of COVID-19 symptoms. Only 23 (33%) were asymptomatic. The most common symptoms were fatigue (34%), muscle weakness or pain (27%), and dyspnea (22%). Vo2 was lower among post-COVID-19 patients compared with control subjects (P = .03, group-by-time interaction P = .007). Reduction in peak Vo2 was due to a combination of chronotropic incompetence (75% of post-COVID-19 patients vs 8% of control subjects, P < .0001) and an insufficient increase in stroke volume during exercise (P = .0007, group-by-time interaction P = .03). Stroke volume limitation was mostly explained by diminished increase in left ventricular end-diastolic volume (P = .10, group-by-time interaction P = .03) and insufficient increase in ejection fraction (P = .01, group-by-time interaction P = .01). Post-COVID-19 patients had higher peripheral oxygen extraction (P = .004) and did not have significantly different respiratory and gas exchange parameters compared with control subjects. Patients recovering from COVID-19 have symptoms associated with objective reduction in peak Vo2. The mechanism of this reduction is complex and mainly involves a combination of attenuated heart rate and stroke volume reserve. •Many patients who recover from COVID-19 report ongoing cardiovascular symptoms.•Abnormally low peak Vo2 is common among patients recovering from COVID-19.•Reduced peak Vo2 is driven by chronotropic incompetence and attenuated SV reserve.